Influence of Current Ratio, Inventory Turnover, and Debt to Equity Ratio to Return on Assets on the Company's Property that are Listed in theIndonesia Stock Exchange - Hade Chandra Batubara (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
The purpose of this research was conducted to find out the influence of the current ratio, inventory turnover, and debt to equity ratio against the return on assets on the company's property that are listed in the indonesia stock exchange.The approach used in this study is the assosiatif approach. While the types of data used in this research is quantitative data in the form of financial statements from the years 2011-2015, the sample used amounted to 7 companies and sources of data from these studies is a report on the company financial property listed on the indonesia stock exchange. Technique of data analysis in this study using multiple linear regression, classic assumption test, test hypotheses and test the coefficient of determination. Processing of data in this study using program SPSS (statistical product and service solution) 22 for windows.The results of this proof proves that partially current ratio was not significant effect against the return on assets, inventory turnover is also partially do not affect significantly to return on assets and debt to equity ratio partially no significant effect against the return on assets. Simultaneously current ratio, inventory turnover and debt to equity ratio effect significantly to return on assets.